The Prototype of ACCDR Model: M-Learning Multimedia Development Design Model Stem-Based for the Online Science Learning - Dian Ratna Sari; Muhaimin Muhaimin; Tedjo Sukmono (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2022)
Online learning is learning carried out without face-to-face but supports the development of virtual academic mobility. It can be integrated with multimedia either in e-learning or m-learning. M-learning is a learning paradigm that takes advantage of developments in wireless and mobile technology. It is flexible, independent, and accessible anywhere and anytime. Integration of science and technology in multimedia m-learning becomes more comprehensive when combined with the principles of Science, Technology, Engineering, and Mathematics. STEM-based multimedia m-learning is developed using a specific development design model. The multimedia m-learning development design model is a structured framework or reference for developing multimedia m-learning. Some of the existing m-learning multimedia development design models do not fully cover the criteria for a suitable model for developing STEM-based multimedia m-learning. One solution that can be given is to develop a new model concept using the F2-O1-S1-A2 type model development procedure through literature studies. The instrument consisted of the model development matrices. Afterward, a STEM-based multimedia m-learning development design model for science learning consisted of five syntaxes, namely: analysis, concepting, design, development, and review. The ACDDR model is a linear diagrammatic-narrative procedural model which is then shortened to the ACDDR model and presented in a prototype form. The ACDDR prototype model is expected to be able to be used for the development of STEM-based multimedia m-learning in the 21st century learning.